2009
DOI: 10.3399/bjgp09x472890
|View full text |Cite
|
Sign up to set email alerts
|

Temporal change in health-related quality of life: a longitudinal study in general practice 1999–2004

Abstract: BackgroundIn order to assess and plan for changing healthcare needs, the lack of available information regarding temporal changes in the health-related quality of life of a population must be addressed. AimThis paper aims to describe such changes over 5 years in a general population. Design of studyLongitudinal postal questionnaire study. Setting UK general practice. MethodThis was a longitudinal postal questionnaire study in two general practice populations, using the generic instrument EQ-5D to measure healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
10
2
Order By: Relevance
“…The small differences could mean that older, less educated, and anxious or depressed patients are slightly less well represented within the study data, causing a small overestimate of the HRQoL values, since all these groups were shown to be more likely to have a lower HRQoL, both here and in previous studies. 27,28 The corroboration of previously reported correlations regarding age, 25,27 sex, [29][30][31][32] smoking status, 28,29 and higher education 33 are important not only to back up previous research, but also to validate the ability of the present results to represent the general population sample. However, although the differences are significant, the effect sizes are small and must be viewed within the context of the minimal important differences for EQ-5Dindex and EQ-5Dvas, which are as yet not fully determined.…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 78%
“…The small differences could mean that older, less educated, and anxious or depressed patients are slightly less well represented within the study data, causing a small overestimate of the HRQoL values, since all these groups were shown to be more likely to have a lower HRQoL, both here and in previous studies. 27,28 The corroboration of previously reported correlations regarding age, 25,27 sex, [29][30][31][32] smoking status, 28,29 and higher education 33 are important not only to back up previous research, but also to validate the ability of the present results to represent the general population sample. However, although the differences are significant, the effect sizes are small and must be viewed within the context of the minimal important differences for EQ-5Dindex and EQ-5Dvas, which are as yet not fully determined.…”
Section: Strengths and Limitations Of The Studysupporting
confidence: 78%
“…16 QoL instruments are also needed as outcome indicators to calculate qualityadjusted life years and cost-effectiveness of therapy and care-delivery interventions. The study by Hazell et al showed 17 an autonomous decrease in QoL over a 5-year period, indicating the difficulty of taking a point of reference. Questions arise around the validity of health-related QoL measures; for example, which cultural and economic influences interfere with health related QoL?…”
Section: Quality Of Lifementioning
confidence: 99%
“…16,17 Both studies are based on postal surveys carried out in the registered population of two general practices. The surveys included the EQ-5D: a generic QoL instrument covering the five dimensions of mobility, self-care, usual activities, pain/discomfort, and anxiety/depression, from which an index score is calculated.…”
Section: Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Available longitudinal studies are based only on small numbers, [5][6][7][8][9][10][11] have short follow-up periods of 6-18 months, 5,6,8,9,11,12 and/or did not investigate the development of factors influencing HRQoL, but included the factors only at one fixed point in time. 13,14 As a result, there are insufficient data to derive practical considerations for GPs on which changes in influencing factors might support patients in maintaining or improving their HRQoL. In light of this, factors affecting the course of patients' HRQoL over 4.5 years were investigated in a representative cohort of 1968 older (aged ≥78 years) primary care patients.…”
Section: Introductionmentioning
confidence: 99%